Antimicrobial nanospheres thin coatings prepared by advanced pulsed laser technique - Holban, Alina Maria; Grumezescu, Valentina; Grumezescu, Alexandru Mihai; Vasile, Bogdan Ştefan; Truşcă, Roxana; Cristescu, Rodica; Socol, Gabriel; Iordache, Florin (Beilstein Journal of Nanotechnology, 2014)
We report on the fabrication of thin coatings based on polylactic acid-chitosan-magnetite-eugenol (PLA-CS-Fe3O4@EUG) nanospheres by matrix assisted pulsed laser evaporation (MAPLE). Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) investigation proved that the homogenous Fe3O4@EUG nanoparticles have an average diameter of about 7 nm, while the PLA-CS-Fe3O4@EUG nanospheres diameter sizes range between 20 and 80 nm. These MAPLE-deposited coatings acted as bioactive nanosystems and exhibited a great antimicrobial effect by impairing the adherence and biofilm formation of Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) bacteria strains. Moreover, the obtained nano-coatings showed a good biocompatibility and facilitated the normal development of human endothelial cells. These nanosystems may be used as efficient alternatives in treating and preventing bacterial infections.
Keywords: antimicrobial; chitosan; magnetite nanoparticles; nanospheres; P. aeruginosa; polylactic acid; S. aureus